Advanced Methodology for Obtaining Early Warning Information and Safety Confirmation Information in Disaster using Drones with Quasi-Zenith Satellite System (QZSS) Receivers and Smartphones - HONGO, Nobuo; HIRATA, Terumitsu (Journal of the Eastern Asia Society for Transportation Studies, 2024)
The government emergency radio system is being developed and operated by the local authority for information sharing on disaster prevention, emergency rescue, and disaster recovery in local areas. In recent years, the quasi-zenith satellite system (QZSS) has been introduced to provide this information. This process is expected to be improved using drones with QZSS Receivers, and smartphones.This study analyzes the behavior of the residents and local authorities in past disasters and the characteristics of the region, propose a solution for the lack of information sharing by utilized QZSS, drones and smartphones. Moreover, it also proposes the most efficient method of gathering information about the conditions of disaster victims using techniques such as drones approaching the vicinity of disaster victims with smartphones.